Nicotine-Induced Neurogenic Relaxation in the Mouse Colon: Changes With Dextran Sodium Sulfate-Induced Colitis - Ikuo Murakami; Yuri Hamada; Satoshi Yamane; Hiromichi Fujino; Shunji Horie; Toshihiko Murayama (Elsevier, 2009)
Nicotine has been shown to reduce both tone and muscular activity in the human colon by releasing nitric oxide (NO) from nerves. To our knowledge, however, the effect of nicotine on mouse colon has not been elucidated, and the response in tissue from ulcerative colitis (UC) has not been investigated. We examined nicotine-induced responses in colon from control mice and mice with dextran sodium sulfate (DSS)-induced UC. In controls, bath application of nicotine caused a transient relaxation in longitudinal preparations from the transverse and distal colons but not from the rectum. The response was observed in the presence of bethanechol, abolished by treatment with tetrodotoxin and hexamethonium, and mediated partially (>50%) by the NO pathway. In longitudinal preparations of the distal colon from DSS-treated mice, spontaneous contractions decreased markedly, and nicotine caused contraction without relaxation in half of the preparations tested. Nicotine-induced relaxation in the presence of bethanechol was significantly decreased in the DSS-treated distal colon without changing bethanechol-induced contractions. These data suggest that 1) responses to nicotine differ dependent on colon regions, 2) DSS treatment predominantly caused nicotine-sensitive neurogenic changes in distal colon, and 3) DSS treatment may reverse the direction of nicotine-evoked responses in the colon, in mice. Keywords:: mice distal colon, motility disorder, nicotine, nitric oxide, ulcerative colitis